Pengaruh Wisata Budaya Museum Puro Pakualaman Yogyakarta Terhadap Minat Pengunjung - Hari Putri, Emmita Devi (Sekolah Tinggi Pariwisata AMPTA, 2017)
The State of Indonesia is a country that has a lot of natural beauty and culture so it is worth to be maintained and preserved in order to bring tourists both local tourists, archipelago and overseas. One of the city that has a cultural tourism attraction is the city of Yogyakarta, which Yogyakarta culture must be maintained and preserved.Cultural tourism becomes an important aspect in the development of a tourism area especially the city of Yogyakarta, which has a variety of uniqueness-cultural uniqueness to be developed into tourist destinations that can be consumed by the tourists.Museum as an object and tourist attraction in the tourism industry because the museum is classified as a tourist attraction of human works which tourist attraction is one of the important elements.ne of the museums in Yogyakarta as a tourist attraction is Puro Pakualaman museum located on Sultan Agung Yogyakarta street, this museum has many potentials that can bring many visitors as a cultural tourism attraction, cultural awareness education and also to emphasize the image of the identity of a nation.The interest of visitors to visit Puro Pakualaman museum as a tourist destination is still very small compared to other tourist destinations.The attraction of Puro Pakualaman museum in the form of frequent substitution of soldiers in Javanese language is Bregodo, archery (jemparingan), various dances ranging from classical dance to modern dance, wayang, various types of historical relics that are still original and not a replica. The research method used in this research is quantitative research method by taking data through questionnaire data, then analyzed by using simple linear regression analysis to know the existence of influence between museum culture variable (X) to visitor interest (Y).The result of the research is (1) tourism culture of museum (X) influence to visitor interest (Y), with regression equation is Y = 16, 798 + 0,228; (2) Hypothesis test that H0 is rejected and Ha accepted meaning there is influence that significant between museum culture tourism to visitor interest with result of sig 0,00